1987
DOI: 10.1254/jjp.45.559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of .GAMMA.-oryzanol and cycloartenol ferulic acid ester on cholesterol diet induced hyperlipidemia in rats.

Abstract: Abstract-Hypolipidemic effects of r-oryzanol (OZ) and cycloartenol ferulic acid ester (CAF) on the hyperlipidemia induced by ingestion of a high cholesterol diet (HCD) in male Sprague-Dawley rats were investigated. The test drugs were given orally and intravenously, daily for 12 days with the HCD feeding. The oral administration with OZ and CAF at 100 mg/kg daily for 6 or 12 days did not ap parently prevent the hyperlipidemia induced by HCD-feeding. The intravenous administrations with OZ and CAF at 10 mg/kg f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…5 . The hypolipidemic effects described by Sakamoto et al 6 and Wilson et al 8 were generated by far higher levels of γ-oryzanol than those administered in the present study. Because to synthesize the same amounts of FMO, FDO and FO as those used in their animal feeding experiments is laborious, we supplemented the animal diet with 90 ppm of each in the present study.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…5 . The hypolipidemic effects described by Sakamoto et al 6 and Wilson et al 8 were generated by far higher levels of γ-oryzanol than those administered in the present study. Because to synthesize the same amounts of FMO, FDO and FO as those used in their animal feeding experiments is laborious, we supplemented the animal diet with 90 ppm of each in the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…contain γ-oryzanol, which is a mixture of ferulic acid-triterpenyl alcohol esters 1 with hypolipidemic effects, whereas ferulic acid and its oligosaccharides have physiological activities against diabetes mellitus 2,3 , hyperglycemia 4 and high blood pressure 5 . Sakamoto et al 6 investigated the effects of γ-oryzanol and cycloartenol ferulic acid ester on hyperlipidemia induced in rats by consuming a high cholesterol diet. The intravenous administration of γ-oryzanol and cycloartenol ferulic acid ester at 10 mg/kg body weight for six days signifi cantly inhibited increases in serum total cholesterol, phospholipids and free cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Sakamoto et al [137] reported that gamma-oryzanol and cycloartenol ferulate have an anti-hyperlipidaemic action and identified that intravenous administration creates more remarkable effects than oral administration due to a direct inhibition of the lipid metabolism. Furthermore, ferulic acid that has been absorbed and metabolised demonstrated an intrinsic hypolipidaemic effect in several studies [138,139].…”
Section: Gamma-oryzanolmentioning
confidence: 99%
“…2 mL of coconut oil per day), along with free access to standard rat feed for inducing the experimental hyperlipidemia-like condition (Sakamoto et al, 1987). The animals were divided into four groups (i.e.…”
Section: In Vivo Pharmacodynamic Studiesmentioning
confidence: 99%